[RETRACTED] Production competitiveness of regional sorghum genotypes against new, enhanced varieties and their morphological traits in Gunung Kidul, Yogyakarta, Indonesia - ARIF MUAZAM; BUDI SETIADI DARYONO; KRISTAMTINI KRISTAMTINI (Society for Indonesian Biodiversity, 2023)
Abstract. Muazam A, Daryono BS, Kristamtini. 2023. Production competitiveness of regional sorghum genotypes against new, enhanced varieties and their morphological traits in Gunung Kidul, Yogyakarta, Indonesia. Biodiversitas 24: 4943-4948. Sorghum is an important cereal crop after rice, maize, wheat and barley. Sorghum can be a potential local food to support national food security and to anticipate the threat of a world food crisis. One effort that can be made is to optimize the land by using adaptive sorghum varieties planted during the rainy season. Various new superior varieties have been released through the Ministry of Agriculture, but the germplasm with a potential to be local food has not been utilized optimally. Several studies on sorghum have been carried out from both cultivation and post-harvest aspects, but to continue the research relay and to participate in meeting national food needs, characterization of local varieties needs to be carried out as a first step in plant breeding activities. This study aims to determine the performance of six genotypes of new high-yielding sorghum varieties and local varieties grown during the rainy season in Karangmojo Village, Karangmojo Sub-district, Gunungkidul District, Yogyakarta Province, from October 2022 to March 2023. The design used was a Randomized Block Complete Design, with 5 repetitions. The results showed the significantly different effect of genotypes on the parameters of plant height, panicle length, panicle width, 1000 seed weight, flowering age, stem diameter, harvesting age, panicle weight per plot, and production per hectare.